Comparing two strategies of counter-defense against plant toxins: a modeling study on plant–herbivore interactions - Chakraborty, Suman; Gershenzon, Jonathan; Schuster, Stefan (Frontiers in Ecology and Evolution, 2023)
Various herbivorous insects prefer toxic plants as their hosts, although this may appear paradoxical. They have evolved specific adaptations (called counter-defenses) against the toxins.For example, the two-component chemical defense system of plants of the Brassicaceae family against herbivores consists of glucosinolates (GLSs) and the activating enzyme myrosinase. GLS hydrolysis by myrosinase leads to isothiocyanates (ITCs), which are toxic and deterrent to many insect herbivores. Two different types of counter-defenses can be distinguished: a preemptive counter-defense that prevents the GLSs from being hydrolyzed to ITCs due to metabolic redirection and direct counter-defense, where the ITCs are formed, but then metabolized to non-toxic conjugates. In general, preemptive counter-defense is only a possibility if the plant stores a precursor of the toxin, which is activated upon attack. Preemptive counter-defense is believed to be more efficient due to the lower exposure to ITCs, but this has not been welldemonstrated experimentally. Here, we derive on theoretical grounds the conditions under which preemptive counter-defense reduces exposure to ITCs compared to direct counter-defense by studying the dynamics of GLS defense and counter-defense with two separate ordinary differential equation models. Our models first deal with how leaf material of a plant (or patch of plants) are ingested by a group of insect herbivores, where the number of susceptible leaves on the plant(s) and the number of insects in the group are taken as constants. Next, we model how herbivory transfers the GLSs to the insect gut with the leaf material. Thereafter, we describe the insects' exposure to toxins by deriving the dynamics of ITCs in the gut during feeding with the two types of counter-defenses. By calculating the area under the curve(s) (AUC) of the ITCs concentrations, we show, based on empirical data, that herbivores with a preemptive detoxification system are usually less exposed to ITCs. In addition, our models explain how the decline in the level of ITCs is achieved by both counter-defenses, which helps to understand the overall mechanisms and benefits of these techniques.